Association of Microcirculation Parameters with Mortality in Patients with Coronary Artery Disease Combined with COVID-19 - Netiazhenko, Vasyl Z.; Mostovyi, Serhii E.; Gurianov, Vitalii G. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To investigate the association of microcirculation parameters with deaths in patients with coronary artery disease and COVID-19. Materials and methods. From January 2020 to December 2022, 79 patients with coronary artery disease (CAD) without COVID-19, 127 patients with CAD and COVID-19, and 180 patients with COVID-19 without CAD were examined at the clinical sites of the Bogomolets National Medical University. The control group consisted of 37 healthy volunteers. Digital capillaroscopy (DC) was performed to assess the caliber and length of arterial and venous parts of the capillaries, as well as velocity of red blood cells therein. Laser Doppler flowmetry (LDF) was used to measure the microcirculation index and capillary blood flow reserve. Wavelet analysis of the basal LDF signal was also performed and the maximum amplitudes of fluxmotions were measured: endothelial, neurogenic, myogenic, respiratory, and cardiac. All the patients underwent transcranial Doppler monitoring to detect microembolic signals. Results. The greatest damage to the microcirculatory bed was observed in patients with CAD and COVID-19. The risk of death was 6.3% in patients with CAD, 22% in those with CAD combined with COVID-19, and 6.1% in patients with COVID-19. According to the LDF, the risk of death increases at certain values of flux amplitudes, and according to the DC, with a decrease in capillary caliber and blood flow velocity. The index of mortality risk assessment was proposed with the consideration of amplitudes of neurogenic fluxmodes, caliber of venous part of the capillaries, velocity of red blood cells in arterial part of the capillaries, microcirculation index and presence of CAD and/or COVID-19. Conclusions. In patients with CAD and COVID-19, deterioration of microcirculation regulation, decreased erythrocyte velocity and increased microembolic signals were found. It is proposed to use the index for assessing the risk of mortality in patients with COVID-19.